Brain grey matter perfusion in primary progressive multiple sclerosis: Mild decrease over years and regional associations with cognition and hand function. (1st March 2022) - Testud, Benoit; Delacour, Clara; El Ahmadi, Ahmed Ali; Brun, Gilles; Girard, Nadine; Duhamel, Guillaume; Heesen, Christoph; Häußler, Vivien; Thaler, Christian; Has Silemek, Arzu Ceylan; Stellmann, Jan‐Patrick
Abstract: Background and purpose: Extent and dynamic of neurodegeneration in progressive multiple sclerosis (MS) might be reflected by global and regional brain perfusion, an outcome at the intercept between structure and function. Here, we provide a first insight into the evolution of brain perfusion and its association with disability in primary progressive MS (PPMS) over several years. Methods: Seventy‐seven persons with PPMS were followed over up to 5 years. Visits included a 3‐T magnetic resonance imaging with pulsed arterial spin labelling perfusion, the Timed 25‐Foot Walk, 9‐Hole Peg Test (NHPT), Symbol Digit Modalities Test (SDMT), and Expanded Disability Status Scale (EDSS). We extracted regional cerebral blood flow surrogates and compared them to 11 controls. Analyses focused on cortical and deep grey matter, the change over time, and associations with disability on the regional and global levels. Results: Baseline brain perfusion of patients and controls was comparable for the cortex ( p = 0.716) and deep grey matter ( p = 0.095). EDSS disability increased mildly ( p = 0.023), whereas brain perfusion decreased during follow‐up ( p < 0.001) and with disease duration ( p = 0.009). Lower global perfusion correlated with higher disability as indicated by EDSS, NHPT, and Timed 25‐Foot Walk ( p < 0.001). The motor task NHPT showed associations with 20 grey matter regions. In contrast, better SDMT performance correlated with lower perfusion ( p < 0.001) in seven predominantly frontal regions, indicating a functional maladaptation. Conclusions: Decreasing perfusion indicates a putative association with MS disease mechanisms such as neurodegeneration, reduced metabolism, and loss of resilience. A low alteration rate limits its use in clinical practice, but regional association patterns might provide a snapshot of adaptive and maladaptive functional reorganization. Abstract : Neurodegeneration in progressive multiple sclerosis might be reflected by altered brain perfusion, an outcome at the intercept between structure and function. In 77 patients, we observed a decrease of arterial spin labelling (ASL) brain perfusion in a longitudinal setting. Regional association patterns indicate that ASL perfusion might provide a snapshot of adaptive and maladaptive functional reorganization.